Koebner Phenomenon In Type II Hypercholesterolaemia - Hemanthkumar; Mohan Thappe Devinder; Sridhar M G (Wolters Kluwer Medknow Publications, 1999)
A family to type II hypercholesterolaemia is reported for the rare occurrence of Koebner phenomenon at the site of venepuncture and skin biopsy scar.